The discontinuous solutions of Lames equations for a conical defect - O. Reut; N. Vaysfeld (Fracture and Structural Integrity)
In this article the discontinuous solutions of Lames equations are constructed for the case of a conical defect. Under a defect one considers a part of a surface (mathematical cut on the surface) when passing through which function and its normal derivative have discontinuities of continuity of the first kind. A discontinuous solution of a certain differential equation in the partial derivatives is a solution that satisfies this equation throughout the region of determining an unknown function, with the exception of the defect points. To construct such a solution the method of integral transformations is used with a generalized scheme. Here this approach is applied to construct the discontinuous solution of Helmholtzs equation for a conical defect. On the base of it the discontinuous solutions of Lames equations are derived for a case of steady state loading of a medium.